RETROGRADE INTRAMEDULLARY SUPRACONDYLAR NAILING AND DISTAL FEMORAL LOCKING COMPRESSION PLATE IN THE MANAGEMENT OF DISTAL FEMUR FRACTURES – A COMPARATIVE STUDY - SY, NARSIMHULU; S, HARI KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study is to assess the efficacy of retrograde intramedullary interlocking supracondylar nailing and distal femoral locking compression plate in the management of distal femur fractures. Methods: The present prospective study consists of a total of 36 cases with extra-articular supracondylar fractures of the femur between the age group of 21–70 years. Participants were randomly allocated to group 1 treated with distal femoral locking compression plate fixation and group 2 treated with retrograde intramedullary interlocking supracondylar nailing technique. Post-operatively, all the cases were followed up in regular intervals to assess the functional outcome using the American Knee Society score. Results: Road traffic accidents (80.56%) were the most common cause of injury. The average surgical duration (108 min and 90.14 min), duration of fracture union (12.48 weeks and 11.08 weeks), and blood loss (339.8 ml and 236.6 ml) was better in the nailing group than the plating group, respectively. The overall outcome was comparable between the two study groups. Conclusion: The supracondylar nailing technique has better functional outcomes in terms of less fracture union time, less operative duration, and minimal operative blood loss. Supracondylar nailing technique was effective and better in soft tissue damage control.